A Bioinspired Triple‐Hierarchical Superhydrophobic Surface with Exceptional Robustness to Water Impingement. Issue 3 (29th November 2022) - Chung, Soochan; Riley, Cameron; Taylor, Hayden
Abstract : Bioinspired surfaces have great potential for self‐cleaning, condensation acceleration, and drag reduction. However, manufactured biomimetic surfaces typically feature only one or occasionally two length scales of surface topography and do not fully recapitulate the structure and function of natural textures. Herein, a triple‐hierarchical superhydrophobic surface (TriSS) inspired by water‐repellent lotus leaves is introduced, which consist of arrays of microprotrusions with various sizes, grooves between the protrusions, and a covering of nanoscale hairs. The TriSS surface is manufactured by forming an array of microdomes through photolithography and thermal reflow. These microstructures are transferred, by casting, to an elastomer, which is then augmented with surface wrinkles by the relaxation of biaxial stress in an oxidized surface layer. Conformal growth of a nanoporous zinc oxide film and fluorosilanization adds further surface detail. The TriSS surface achieves a sessile water contact angle up to 174.3 ± 0.3° and contact angle hysteresis down to 9.9 ± 0.3° via the very limited liquid–solid contact enabled by the surface topography. The surface also captures and retains a stable air layer, which resists water impingement even when submersed to 20 cm depth for more than 200 h. The TriSS process offers a scalable route to water repellence in industrial applications. Abstract : Inspired by the lotus leaf, an artificial three‐scale structure is engineered, composed of microdome arrays with heterogeneous diameters and heights, interstitial microwrinkles produced by buckling of the bilayered polymer surface, and a zinc oxide nanoporous film. Water contact angles up to 174.3 ± 0.3°, hysteresis down to 9.9 ± 0.3°, and effective resistance to water impingement during immersion are achieved.